2008
DOI: 10.1007/s10681-008-9737-y
|View full text |Cite
|
Sign up to set email alerts
|

Pre and posthaustorial resistance to rusts in Lathyrus cicera L.

Abstract: Lathyrus cicera has a high potential as fodder crop in dry areas, but can in particular environments be damaged by rust. Little is known on the availability of resistance against rust fungi and the underlying mechanisms in L. cicera germplasm. The present study assessed and characterised macro and microscopically the resistance to rust fungi Uromyces pisi and U. viciae-fabae, in a collection of L. cicera accessions. A wide range of disease reaction was found in the germplasm collection against the different ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…In both, L. cicera and L. sativus , resistant genotypes restrict the formation of haustoria resulting in a high percentage of early aborted fungal colonies, a decreased number of haustoria per colony and reduced intercellular growth of infection hyphae compared to susceptible genotypes from the same species 6,11,13 . Still, L. sativus is generally more resistant than L. cicera .…”
Section: Discussionmentioning
confidence: 99%
“…In both, L. cicera and L. sativus , resistant genotypes restrict the formation of haustoria resulting in a high percentage of early aborted fungal colonies, a decreased number of haustoria per colony and reduced intercellular growth of infection hyphae compared to susceptible genotypes from the same species 6,11,13 . Still, L. sativus is generally more resistant than L. cicera .…”
Section: Discussionmentioning
confidence: 99%
“…Directional growth of the germ tube and formation of appressorium are controlled by the stimuli originating from the host [30]. It seems that, for the first time, an alternative 'avoidance' or prepenetration mechanism is apparent in Cyperus -S. rolfsii interaction, which operates after the contact of parasite on the host epidermal cell [31,32]. However, we failed to observe the extension of hyphae inter-and intracellularly.…”
Section: Discussionmentioning
confidence: 63%
“…Incomplete resistance identified in pea against U. pisi is not therefore based on HR, fitting the definition of Partial Resistance (PR) (Parlevliet & Van Ommeren 1975). Similarly, PR against rusts has also been reported in other legumes such as faba bean (Sillero et al 2000;Herath et al 2001), common bean (Statler & McVey 1987), grass pea (Vaz Patto et al 2009a), chickling pea (Vaz Patto et al 2009b) and chickpea (Madrid et al 2008;Sillero et al 2012).…”
Section: Screening and Sources Of Resistancementioning
confidence: 83%
“…Neither was host cell death observed later (6 DAI) (Barilli et al 2009b) discarding also the possibility of late-acting HR that was reported in other interactions such as L. cicera-U. viciae-fabae (Vaz Patto et al 2009b), V. faba-U. viciae-fabae (Herath et al 2001;Sillero & Rubiales 2002) and barleyPuccinia hordei (Niks 1986).…”
Section: Screening and Sources Of Resistancementioning
confidence: 90%